Economy and Ritual in the Condesuyos of Arequipa: Shepherds and Weavers of the XIX Century - Millones Santa Gadea, Luis (1975)
On October 6, 1812, the Regency of the Kingdom of Spain sent a 36-question questionnaire to the clergy of its Peruvian colonies, seeking to have a further perspective of the state of its vassals. The aforementioned document (A. G. I, Audiencia de Lima, legajo 1598) corresponded to the interest in obtaining a diagnosis of the human resources available to the Spanish government in the difficult moments in which the Creole groups were openly fighting for control of the colonies. .